Edukasi “Lima Detik” untuk Meningkatkan Kesadaran Bahaya Makanan Jatuh dan Kebersihan Jajanan Siswa Sekolah Dasar - Matius Paundanan; Sitti Ainun Hikmah (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Food safety among elementary school children remains a public health concern, particularly regarding the habit of consuming dropped food and lack of attention to snack packaging hygiene. Health education is needed to improve students’ knowledge and awareness regarding microbial contamination risks in food. This community service activity aimed to improve students’ understanding of the dangers of dropped food and the importance of snack packaging hygiene through “Five-Second Rule” education. The activity was conducted at Bala Keselamatan Wayu Elementary School, Sigi Regency, Central Sulawesi, involving 26 students from grades I–VI. Methods included interactive lectures, discussions, simulations, simple practices, and evaluation using pre-test and post-test assessments. The results showed an increase in average knowledge scores across all grade groups after the educational intervention. Students in grades V–VI demonstrated the highest improvement compared to other groups. Simulation- and practice-based education proved effective in improving students’ understanding of food safety and clean healthy living behavior. This activity has the potential to be developed as a promotive and preventive strategy in establishing healthy snacking behavior among elementary school children.